Modification of chitosan-based membranes using zeolite for pervaporation separation of isopropanol-water mixtures - Mohd Nawawi, Mohd Ghazali; Hassan, Hashim; Jalil , Abdul Rahim (Universiti Malaysia Sabah, 2003)
In this paper, the performances of zeolite-filled chitosan membranes were studied. The zeolite filled chitosan membrane was prepared by adding a calculated amount of zeolite into the aqueous acetic acid solution and mixing thoroughly until the solution become homogenous. A pre-weighed quantity of chitosan was added into the solution and was strirred overnight. Membrane was treated and dried in the similar way as for the homogenous chitosan membrane. Scanning Electron Micrograph analysis shown that the membrane exhibit a dense structure. The dry membrane samples were weighed and subsequently immersed in a 90 wt% isopropanol-water mixture for 72 h at room temperature. The effective membrane area is 52.8 cm2. The downstream pressure was maintained at 3-5 mmHg by using a vacuum pump. The permeation rate was determined by measuring the weight of permeate collected in a given period of time. The membrane characteristics were determined through swelling test and the pervaporation dehydration of isopropanol-water mixtures. The results showed that, membrane filled with zeolite exhibited a higher permeation flux with some loses in the separation factor. The optimum value for zeolite content in the membrane is about 0.1wt%. At higher zeolite content in the membrane, the separation factor decreased very significantly which is due to less selective 'leaks' formed around the zeolite crystals during preparation.